A Glimpse of Programmed Cell Death Among Bacteria, Animals, and Plants - Zhuang, Jun; Xie, Li; Zheng, Luping (Frontiers in Cell and Developmental Biology, 2022)
Programmed cell death (PCD) in animals mainly refers to lytic and non-lytic forms. Disruption and integrity of plasma membrane as hallmarks of lytic and apoptotic cell death, respectively.These lytic cell death programmes can prevent the hosts from microbial pathogens. Key to our understanding of these cases are pattern recognition receptors (such as TLRs in animals and LRR-RLKs in plants) and Nod-like receptors (NLRs). Herein, I emphatically discuss the biochemical and structural studies that have clarified the anti-apoptotic and proapoptotic functions of Bcl-2 family proteins during intrinsic apoptosis, and how caspase 8 among apoptosis, necroptosis and pyroptosis set the switchable threshold and integrate innate immune signaling, and that have compared the similarity and distinctness of apoptosome, necroptosome and inflammasome. I recapitualte that necroptotic MLKL pore, and pyroptotic gasdermin pore, HR-inducing resistosome and mitochondrial Bcl2 family all can form ion channels, which all directly boost membrane disruption. Comparing the conservation and unique aspects of PCD including ferrroptosis among bacetria, animals and plants, the commonly shared immune domains including TIR-like, gasdermin-like, caspase-like, MLKL/CC-like etc. act as arsenal modules to restructure the diverse architectures for commit PCD suicide upon stresses/stimuli for host community